Study of the thermogravimetric analysis application to determine volatile impurities for the reference standards certification - Леонтьев, Дмитрий Анатольевич; Воловик, Наталья Валерьевна; Бевз, Елена Валерьевна; Ващенко, Ольга Валерьевна; Будянская, Лилия Владимировна (ScienceRise: Pharmaceutical Science, 2016)
Aim. To study thermal gravimetric analysis (TGA) application for the reference standards certification, considering the uncertainty metrological concept of the State Pharmacopoeia of Ukraine. Methods. Thermogravimetric analysis, mathematical statistics methods. Results. TGA application to determine volatile impurities for the reference standards certification was studied, considering the requirements for making the reliable conclusion about quality of medicines (95 %). Requirements to the volatile impurities content uncertainty were formulated. It has been found, that measurement uncertainty evaluation for the volatile impurities determination, using TGA method, meets the strictest requirements for the pharmaceutical reference standards certification. Conclusion. It has been shown, that TGA method allows the use of minimum weighed portions, typical for pharmaceutical analysis practice: 10 mg for quantitative determination, 5 mg or less for purity tests, 10 mg for homogeneity tests, which is the strictest requirement for pharmaceutical reference standards